PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS PENGAJUAN DAN PEMECAHAN MASALAH PADA MATAKULIAH PROGRAM LINEAR PRODI PENDIDIKAN MATEMATIKA IKIP PGRI BOJONEGORO - Dwi Erna Novianti; Anis Umi Khoirotunnisa (Universitas PGRI Madiun, 2016)
This research and development is meant to produce a product of learning set based on problem submission and problem solving in Linear program course in the department of mathematics Teaching of IKIP PGRI Bojonegoro. The development of this set includes Lesson Plan, worksheet and a test of study result. This research is done within the department of Mathematics Teaching of IKIP PGRI Bojonegoro in the academic year of 2015/2016 from March to June 2016. The population of this research are sixth semester students. The research method used in this research is developmental research, while the model of developmental research used is developmental Thiagarajan which had been modified from four steps into three steps model namely:defining, designing, and developing. The data collection methods used in this research are documentation, Questionnaire, and learning result. The result shows that the set of learning in 4-D model which had been modified, resulted in a good learning set of JUCAMA model because the set of learning produced is a valid set based on the expert and based on the test in the field shows the data as the response toward positive learning, and the result of the test had fulfilled a good validation criteria, reliability as well as its sensitiveness.